Analysis of the enterprise operating expenses and ways of improvement of their accounting - Grytsay, O.; Pankiv, M.; Kut, D.; Wojtan, G. (Видавництво Львівської політехніки, 2021)
Activities of industrial enterprises are associated with continuous consumption of certain types of resources, so expense accounting plays a crucial role in determining the enterprise efficiency. Accounting procedures occupy a key place in information support system of any enterprise, since the original information on the enterprise activities in the form of financial statements and internal documentation (source documents, journals and ledgers) is essential in order to meet the needs of internal and external users. It is particularly important to account for operating expenses, which forms information about the use of materials, labor and other resources involved in the production process. Properly organized accounting and analytical information on operating expense ensures fair and accurate assessment of the enterprise production process and provide effective management decision-making. The purpose of the scientific paper is to analyze operating expenses, organization and methodology of the accounting process at the enterprise and to develop practical recommendations for improving the accounting for operating activity.This goal necessitates the solution of the following tasks: determine the nature and classification of operating expenses; analyze the dynamics and structure of operating expenses; develop the suggestions concerning the improvement of registration-analytical information of operating expenses. The used research methods and general characteristics of paper. The authors applied the method of literature review to justify the relevance of the chosen research topic. On the basis of the comparative method the main economic indicators of activity, in particular dynamics and structure of operating expenses according economic elements and according items of calculation were defined. On the basis of system analysis and synthesis, proposals on the composition of items of production costing and on the introduction of classification of expenses by groups in terms of relevant items of general production expenses, administrative, marketing expenses and other operating expenses were formed.
Keywords: operating expenses; revenue; financial result; analysis; accounting; M; 41; 658; 338; 65.012.8